Illustrative case studies in the return of exome and genome sequencing results. (June 2015) - Amendola, Laura M; Lautenbach, Denise; Scollon, Sarah; Bernhardt, Barbara; Biswas, Sawona; East, Kelly; Everett, Jessica; Gilmore, Marian J; Himes, Patricia; Raymond, Victoria M; Wynn, Julia; Hart, Ragan; et al.
Whole genome and exome sequencing tests are increasingly being ordered in clinical practice, creating a need for research exploring the return of results from these tests. A goal of the Clinical Sequencing and Exploratory Research (CSER) consortium is to gain experience with this process to develop best practice recommendations for offering exome and genome testing and returning results. Genetic counselors in the CSER consortium have an integral role in the return of results from these genomic sequencing tests and have gained valuable insight. We present seven emerging themes related to return of exome and genome sequencing results accompanied by case descriptions illustrating important lessons learned, counseling challenges specific to these tests and considerations for future research and practice.